Formation of Tissue-Resident CD8 + T-Cell Memory - Dijkgraaf, Feline E; Kok, Lianne; Schumacher, Ton N M (Cold Spring Harbor perspectives in biology, 2021)
Resident memory CD8 T (Trm) cells permanently reside in nonlymphoid tissues where they act as a first line of defense against recurrent pathogens. How and when antigen-inexperienced CD8 T cells differentiate into Trm has been a topic of major interest, as knowledge on how to steer this process may be exploited in the development of vaccines and anticancer therapies. Here, we first review the current understanding of the early signals that CD8 T cells receive before they have entered the tissue and that govern their capacity to develop into tissue-resident memory T cells. Subsequently, we discuss the tissue-derived factors that promote Trm maturation in situ. Combined, these data sketch a model in which a subset of responding T cells develops a heightened capacity to respond to local cues present in the tissue microenvironment, which thereby imprints their ability to contribute to the tissue-resident memory CD8 T-cell pool that provide local control against pathogens.